2016
DOI: 10.1038/srep38933
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Hollow Fe2O3 Nanorods and Nanospheres by Nanoscale Kirkendall Diffusion, and Their Electrochemical Properties for Use in Lithium-Ion Batteries

Abstract: A novel process for the preparation of aggregate-free metal oxide nanopowders with spherical (0D) and non-spherical (1D) hollow nanostructures was introduced. Carbon nanofibers embedded with iron selenide (FeSe) nanopowders with various nanostructures are prepared via the selenization of electrospun nanofibers. Ostwald ripening occurs during the selenization process, resulting in the formation of a FeSe-C composite nanofiber exhibiting a hierarchical structure. These nanofibers transform into aggregate-free ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Hollow nanostructured transition metal oxide anode materials and their corresponding electrochemical performances are presented in Figure 9 . Hollow Fe 2 O 3 nanorods and nanospheres in Figure 9 a were synthesized via selenization of a precursor nanofiber and a subsequent oxidation reaction [ 125 ]. The hollow nanorod exhibited typical CVs of Fe 2 O 3 and the following electrochemical reactions: (i) lithium insertion at around 1.6 and 1V to form Li 2 Fe 2 O 3 (cubic), the complete reduction of iron to Fe 0 , and Li 2 O formation/SEI formation at around 0.7 V during the first cathodic scan; (ii) the oxidation of iron from Fe 0 to Fe 2+ at 1.7 V and Fe 3+ at 1.85 V during anodic scans; and (iii) the reduction of iron from Fe 3+ to Fe 0 at around 0.8 V during the following cathodic scans [ 120 , 126 ].…”
Section: Conversion Reaction-based Storage Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hollow nanostructured transition metal oxide anode materials and their corresponding electrochemical performances are presented in Figure 9 . Hollow Fe 2 O 3 nanorods and nanospheres in Figure 9 a were synthesized via selenization of a precursor nanofiber and a subsequent oxidation reaction [ 125 ]. The hollow nanorod exhibited typical CVs of Fe 2 O 3 and the following electrochemical reactions: (i) lithium insertion at around 1.6 and 1V to form Li 2 Fe 2 O 3 (cubic), the complete reduction of iron to Fe 0 , and Li 2 O formation/SEI formation at around 0.7 V during the first cathodic scan; (ii) the oxidation of iron from Fe 0 to Fe 2+ at 1.7 V and Fe 3+ at 1.85 V during anodic scans; and (iii) the reduction of iron from Fe 3+ to Fe 0 at around 0.8 V during the following cathodic scans [ 120 , 126 ].…”
Section: Conversion Reaction-based Storage Materialsmentioning
confidence: 99%
“… Schematic illustrations of hollow nanostructured transition metal oxide anode materials and corresponding electrochemical performances. ( a ) Fe 2 O 3 nanostructures (reprinted with permission from [ 125 ]; copyright 2016 Springer Nature), ( b ) hollow Co 3 O 4 nanostructure (reprinted with permission from [ 127 ]; copyright 2019 Royal Society of Chemistry), and ( c ) hollow NiO nanofiber (reprinted with permission from [ 130 ]; copyright 2019 Elsevier). …”
Section: Figurementioning
confidence: 99%
“…Various α-Fe 2 O 3 nanostructures with different morphologies such as nanoparticles 8,12 , nanowires (NWs) 13,14 and nanotubes (NTs) 15,16 have already been successfully synthesized. Additionally, several works reported, recently, the synthesis of hollow iron oxide nanoparticles through the Kirkendall effect 1317 .…”
Section: Introductionmentioning
confidence: 99%
“…Given that fundamental properties of materials can be tuned through morphology and size, precise structure control is of utmost importance 18,19 . For example, nanostructured α-Fe 2 O 3 has been studied as an anode material for lithium ion batteries for its high capacitance and it was demonstrated that higher porosity is advantageous over repetitive cycling 15 ; this way a nanotube would provide better results than a nanorod, for example. Also, quantum confinement in very thin nanostructures, such as nanotubes with extremely thin walls, can be used to tune the band edges and band gap of a semiconductor for photoelectrochemical applications 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The lithium ion battery anode made from the fibers showed improved cycling performance and rate capability. There are many other researchers who reported their work on this application [2][3][4][5][6][7]. For example, in the work performed by Xu et al [4], iron oxide/carbon nanofibers (FeOx/CNFs) were prepared by electrospinning the FeCl 3 •6H 2 O-polyacrylonitrile (PAN) precursors and heat treating at different temperatures.…”
Section: Introductionmentioning
confidence: 99%